Experimental Method to Find the Flux Variation on the Receiver of Central Receiver System - Kashinath H. Munde, Vikaskumar K. Mehtre, Mahesh P. Kumbhare, Ganesh E. Kondhalkar (Mathematical Statistician and Engineering Applications, 2022)
Concentrating solar technologies can be used for power generation as well as industrial process heating. A point focusing solar collector forms a flux distribution on the receiver plate in two dimensions at the focal plane. A tool or method for analyzing the flux distribution nature can be great helpful to know the optical quality of the receiver. Experiments needs to be carried out in the focal region of the concentrating collector to know the flux distribution on the receiver plate. Behavior of the flux distribution are measured by flux mapping techniques and also these methods can provide accurate results, but the equipment of this method is specialized and costly. A simple method need to estimate the optical quality like flux distribution and focus size for central receiver system. Thermocouple method is used for finding the distribution of flux density on the receiver. This information is helpful in the design of the receiver size, shape and the choice of the material.